Public Policy in the Digital Era: Transformation of Political Communication - Kristomei Sianturi (PT Publikasiku Academic Solution, 2023)
Communication is a basic human activity in everyday life, communication is an important component for the survival of humans or community groups. The current development of information technology is able to change social, cultural and even political communication patterns in Indonesia and even the world so that in practice political communication has now begun to shift from conventional to social media. The massive use of the internet among the public is an indication of the digital era which is giving rise to unpredictable changes in the direction of the pace. This research aimed to find out what kind of public policies are made in the current digital era. The research uses a qualitative research method with a library study method as the data collection method. This literature study aims to enrich the author's information as well as enrich data or research materials in the field. The results of this research are that public policy in the digital era has had a positive impact or influence on the transformation of political communication in Indonesia, and social media is also able to change political communication patterns from conventional to social media by utilizing applications such as Facebook and Instagram to reach its target audience. and gain a political voice.